TRANSFORMATION OF DAKWAH MEDIA IN INSPIRING MUSLIMAH IN THE DIGITAL ERA - Badrah Uyuni; Rabiah Al Adawiyah; Raihanatul Quddus; Kasyifatudduja Kasyifatudduja (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
In the contemporary digital landscape, the role of media in disseminating Islamic teachings and inspiring Muslim communities, particularly mothers, has undergone a significant transformation. This paper explores the evolution of dakwah media and its impact on empowering and inspiring Muslim mothers in the digital era. Through a comprehensive review of literature, the paper examines the utilization of various digital platforms, such as social media, podcasts, and mobile applications, to deliver relevant and engaging dakwah content tailored to the needs and interests of Muslim mothers. Additionally, case studies and examples are analyzed to highlight successful initiatives and strategies employed by dakwah media practitioners in inspiring and empowering Muslim mothers in their spiritual journey and everyday lives. The findings shed light on the transformative potential of dakwah media in shaping attitudes, behaviors, and identities among Muslim mothers in the digital age, while also underscoring the importance of ethical considerations and community engagement in dakwah efforts.